Peran Pembelajaran Homeschooling dalam Membentuk Kecerdasan Intrapersonal - Monica Nur Azizah; Siti Shopiyah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
The background of the authors conducted this research because homeschooling is a home-based education, which allows children to develop according to their own potential. Homeschooling is also a choice that is considered appropriate to provide instruction for gifted children by many parents because the content of learning materials and the way they are provided are adjusted to the circumstances of the students concerned. At Fikar School, we implement community-based homeschooling and have interesting and effective learning methods. Based on the background of the problem, the authors are interested in knowing the role of homeschooling learning in shaping intrapersonal intelligence at Fikar School Rempoa, South Tangerang. The research method used in this research is a descriptive analysis research, by describing the actual situation or facts according to what happened in the field. The approach used is a qualitative approach, with research stages namely observation, interviews, and documentation. Then this study uses data analysis techniques namely data reduction, data presentation and drawing conclusions. his can be proven by the results of the study, namely that at Fikar School strongly applies to the character content of children and it impacts on each child to be able to know the extent of their abilities and awareness of their interests and talents. With a learning process such as this culture habit, it can have a good influence on a child's intrapersonal intelligence, so that it can form good character and make the child's culture to be independent wherever the environment.